Research methodology - Panneerselvam, R., author
This comprehensive text designed for MBA, MCom, MA (Economics), MA (Sociology) and PhD (Management, Commerce, Economics, and Engineering) courses continues to give complete account of concepts and statistical tools of research methodology in its Second Edition. The textbook also serves as a reference for consultants to carryout [sic] projects/consultancies in industries or service organizations.